Due process of law and principle of legality in the interpretation of procedural norms - Passanante, Luca (Pontificia Universidad Católica del Perú, 2021)
In this essay the author highlights the importance of the role of the principle of due process of law, understood as a requirement of procedural legality, which orients the interpretation of procedural norms in order to avoid innovative interpretations that could subvert the procedural rules.

En el trabajo el autor resalta la importancia del rol del principio del debido proceso, entendido como una exigencia de legalidad procesal, lo cual termina orientando la interpretación de las normas procesales a fin de evitar interpretaciones que puedan subvertir las reglas del proceso.
Debido proceso y principio de legalidad en la interpretación de las normas procesales
Keywords: Debido proceso; Principio de legalidad; Interpretación jurídica; https://purl.org/pe-repo/ocde/ford#5.05.00